BPJS Pending Claim Settlement Strategy In Hospital With Management Approach (Planning, Organizing, Actuating, Controlling) - Wijayanti, Rossalina Adi; Dewi, Riskha Dora Candra; Farlinda, Sustin; Nuraini, Novita (P3M Politeknik Negeri Jember, 2023)
The pending claim incident at Citra Husada Hospital Jember reached 33 files in December 2021, impacting health services' sustainability. This study aims to formulate a strategic policy review in the settlement of BPJS pending claims in hospitals with the Planning, Organizing, Actuating, and Controlling management approach. This research is qualitative. Data collection techniques using observation, interviews, documentation, and brainstorming. Test the validity of the data using source triangulation and technique triangulation. Based on the study results, the BPJS pending claim settlement strategy at Citra Husada Hospital Jember was implemented with a Planning, Organizing, Actuating, and Controlling management approach. Planning is carried out by preparing the quality of human resources and SOPs. Implementation of Organizing through coordination between officers and between fields, but there are still incomplete files and different interpretations between fields. Actuating is constrained by the system, while controlling is carried out through scheduled supervision.